Influence of Personality Traits on Motivation and Engagement among Adolescents During Online Education - Rashmi Motwani; Ritu Raj (International Journal of Education Sciences, 2025)
This study investigates how the Big Five personality traits—openness, conscientiousness, extraversion, agreeableness, and neuroticism—affect motivation and engagement among adolescents in online education settings. During the COVID-19 pandemic, online learning became a necessity, but not all students adapted equally. A sample of 600 students aged 16 to 19 years from 30 inter colleges in the Gwalior district participated in this research. Data were collected using a structured questionnaire measuring personality traits and online learning motivation/engagement. SPSS was used for statistical analysis, including Pearson correlation. Results reveal that conscientiousness and openness are positively associated with motivation and engagement, while neuroticism shows a negative correlation. These findings highlight the need for personalized digital learning strategies that consider individual personality differences to improve educational outcomes.
Keywords: Adolescents; Big Five; Engagement; Online education; motivation; personality traits